Static magnetic field increases survival rate of dental pulp stem cells during DMSO-free cryopreservation. (2nd October 2015) - Lin, Shu-Li; Chang, Wei-Jen; Lin, Chun-Yen; Hsieh, Sung-Chih; Lee, Sheng-Yang; Fan, Kang-Hsin; Lin, Che-Tong; Huang, Haw-Ming
Abstract: Successful and efficient cryopreservation of living cells and organs is a key clinical application of regenerative medicine. Recently, magnetic cryopreservation has been reported for intact tooth banking and cryopreservation of dental tissue. The aim of this study was to assess the cryoprotective effects of static magnetic fields (SMFs) on human dental pulp stem cells (DPSCs) during cryopreservation. Human DPSCs isolated from extracted teeth were frozen with a 0.4-T or 0.8-T SMF and then stored at −196 °C for 24 h. During freezing, the cells were suspended in freezing media containing with 0, 3 or 10% DMSO. After thawing, the changes in survival rate of the DPSCs were determined by flow cytometry. To understand the possible cryoprotective mechanisms of the SMF, the membrane fluidity of SMF-exposed DPSCs was tested. The results showed that when the freezing medium was DMSO-free, the survival rates of the thawed DPSCs increased 2- or 2.5-fold when the cells were exposed to 0.4-T or 0.8-T SMFs, respectively ( p < 0.01). In addition, after exposure to the 0.4-T SMF, the fluorescence anisotropy of the DPSCs increased significantly ( p < 0.01) in the hydrophilic region. These results show that SMF exposure improved DMSO-free cryopreservation. This phenomenon may be due to the improvement of membrane stability for resisting damage caused by ice crystals during the freezing procedure.